Influencia de las variables del proceso transesterificación de aceite vegetal usado catalizada con residuos de concreto para obtener biodiesel - Fachin Saavedra, Marlon Estefano (2024)
The study investigates the effect of process variables (oil/methanol ratio, amount of catalyst and reaction time) on the production of biodiesel with concrete waste as catalysts and used oils. The concrete waste was collected at the intersection of Sta. Rosa and Yavari streets, and the used vegetable oil was obtained from FUNDESAB. The research is descriptive-experimental and aims to improve the efficiency of the process. The used oil showed a moisture content of 0.06% and an acidity level of 0.51%. The concrete residues were dried at 100°C for 8 hours, pulverised and weighed in 5 gram samples. They were then calcined at 700°C, 800°C and 900°C for 4 hours to determine the optimum activation temperature. The amount of calcium was evaluated by colorimetric and volumetric methods. The results showed an average maximum biodiesel yield of 70.15% using 4 grams of the catalyst, an alcohol/oil molar ratio of 9/1 and a reaction time of 180 minutes. The analysis of variance revealed a p-value < 0.05 for a significance level α=0.05, indicating significant differences in the biodiesel yields obtained in the different reaction trials. In conclusion, the concrete wastes showed considerable efficiency as catalysts, with an average yield of 70.15%, a slight inferiority was observed compared to the yield obtained with other catalysts.